A comparative study of software process improvement implementation success factors. Issue 9 (10th February 2015) - Niazi, Mahmood
Abstract: Context: It has been observed that software process improvement (SPI) initiatives have been around for more than a decade, yet many companies are still facing SPI implementation challenges. Objective: In this paper, a systematic literature review (SLR) has been conducted, and the results are compared with the previously collected data of SPI implementation success factors. The overarching objective of this research is to gain an in‐depth understanding of success factors that play a positive role in SPI implementation; this will assist SPI managers in better designing and managing SPI programs. We are interested to discover if there are any differences in the success factors identified by the three research strategies used, that is, informal literature review, SLR, and interviews. Method: Data were collected and analyzed using the three research strategies. For informal literature review, the snowballing technique was used. The SLR was conducted for formal literature reviews. For an empirical study, interviews were conducted with Australian SPI practitioners. Results: Results show that (i) senior management commitment and (ii) staff involvement are the frequently cited common SPI success factors in all three research strategies. The results also uncover similarities and differences among the three research strategies regarding the importance of the SPI success factors: (i) SPI awareness is a frequently cited common SPI success factor in interviews and formal literature review, and the Spearman's rank‐order correlation is r s (37) = 0.413, p = 0.011; (ii) reviews are a frequently cited common SPI success factor in formal and informal literature reviews, and the Spearman's rank‐order correlation is r s (37) = 0.517, p = 0.001; and (iii) training and mentoring is a frequently cited common SPI success factor in interviews and an informal literature review, and the Spearman's rank‐order correlation is r s (37) = 0.195, p = 0.247. Conclusions: The understanding of these factors can help both researchers and software development organizations in successfully planning and implementing SPI initiatives. Copyright © 2015 John Wiley & Sons, Ltd.